2022
DOI: 10.1128/spectrum.01269-22
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Complex Interplay between Quorum Sensing and Antibiotic Resistance in Pseudomonas aeruginosa

Abstract: Quorum sensing (QS) is a cell-density-dependent communication system used by a wide range of bacteria to coordinate behaviors. Strategies pertaining to the interference in QS are appealing approaches to control microbial behaviors that depend on QS, including virulence and biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…Using this bacterial model, several studies have demonstrated that QQE may reduce various virulence factors such as motility, biofilm formation, and virulence against model organisms ( Caernorhabditis elegans, Drosophila melanogaster , and mice) (Hraiech et al 2014 , Sikdar and Elias 2020 ). In addition, recent studies have demonstrated that the use of a QQ lactonase can significantly modulate P. aeruginosa PA14 susceptibility or resistance to antimicrobials (Rémy et al 2020 , Sikdar and Elias 2022 ). The synergistic effect of combining the QQE and antimicrobials (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Using this bacterial model, several studies have demonstrated that QQE may reduce various virulence factors such as motility, biofilm formation, and virulence against model organisms ( Caernorhabditis elegans, Drosophila melanogaster , and mice) (Hraiech et al 2014 , Sikdar and Elias 2020 ). In addition, recent studies have demonstrated that the use of a QQ lactonase can significantly modulate P. aeruginosa PA14 susceptibility or resistance to antimicrobials (Rémy et al 2020 , Sikdar and Elias 2022 ). The synergistic effect of combining the QQE and antimicrobials (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The expanding edge of antibiotic resistance, as one of the detrimental souvenirs of this millennium, has encountered us with hazards. The extensive use and misuse of antimicrobial agents result in the rapid resistance development to all antibiotics commonly used in the treatment of P. aeruginosa infection [ [165] , [166] , [167] , [168] , [169] , [170] ]. The high level of resistance to the wide range of antibiotics is due to the multiple mechanisms such as the outer membrane's limited uptake, efflux pump expression, horizontal transfer of antibiotic resistance gene, the activity of drug-degrading enzymes, and production of modification enzymes ( Table-2 ) [ [88] , [89] , [171] , [172] ].…”
Section: Antimicrobial Resistance In P Aeruginosa ...mentioning
confidence: 99%
“…Once the bacterial density reaches its quorum, the OC 12 -HSL/LasR complex positively activates the transcriptional regulation of rhlR , rhlI , lasI , and other virulence genes that are part of its regulon ( 6 ), followed by positive regulation of PqsR, thus producing the Pseudomonas quinolone signals ( 7 , 8 ). Additionally, QS can contribute to behaviors that enable bacteria to resist antimicrobial compounds, e.g., biofilm development ( 9 , 10 ). Selectively interfering with QS systems is one of the novel strategies targeted at disarming virulent opportunistic pathogens such as P. aeruginosa ( 11 , 12 ).…”
Section: Observationmentioning
confidence: 99%